2018
DOI: 10.1080/0163853x.2018.1526032
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Stories: Transportation into Narratives with Strong Protagonists Increases Self-Related Control Beliefs

Abstract: Several studies have shown that narratives can influence readers' beliefs about themselves. In the present study, our goal was to investigate whether stories portraying a strong protagonist can positively influence recipients' beliefs of being in control of events in their own lives (self-related control beliefs). Experiment 1 showed that narratives in both written text and video form with protagonists displaying high versus low self-efficacy can, at least temporarily, affect recipients' own self-related contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 54 publications
1
15
0
1
Order By: Relevance
“…Effects of narratives depend on numerous personality and situational factors. As indicated by an increasing number of studies, in many instances the persuasive effects of narratives depend on the extent to which the reader is transported into a story (e.g., Appel & Richter, 2007, 2010; Green & Brock, 2000, 2002), including effects on personality (Isberner et al, 2019; Richter, Appel, & Calio, 2014). The same might apply to influences of narratives on social–cognitive skills (Mar, 2018a, 2018b).…”
Section: The Role Of Transportation and Transportabilitymentioning
confidence: 99%
“…Effects of narratives depend on numerous personality and situational factors. As indicated by an increasing number of studies, in many instances the persuasive effects of narratives depend on the extent to which the reader is transported into a story (e.g., Appel & Richter, 2007, 2010; Green & Brock, 2000, 2002), including effects on personality (Isberner et al, 2019; Richter, Appel, & Calio, 2014). The same might apply to influences of narratives on social–cognitive skills (Mar, 2018a, 2018b).…”
Section: The Role Of Transportation and Transportabilitymentioning
confidence: 99%
“…This concern extends to media like fairy tales and superhero franchises that involve characters with magical or superhuman powers. These characters serve as role models despite the fantastical elements, as is illustrated by research describing how fans of science fiction and fantasy have translated the positive lessons they see in these stories into real-world actions (e.g., Jenkins, 2012), as well as by studies such as those by Isberner et al (2018), which found that exposure to fairy tales with empowered women characters increased viewers' sense of self-efficacy. The potential role of a demographic match between a viewer and a character is complicated, but not eliminated, when considering narratives that take place in fantastical settings where a characters' heritage or gender can be immaterial, unspecified, or fantastical.…”
Section: Asked a Sample Of Young Adults To Indicate Howmentioning
confidence: 99%
“…Bilandzic and Busselle (2008) also speak of the cultivation of story-consistent beliefs that individuals learn from multiple transportation experiences into narrative worlds. Transportation may also lead indi-viduals to include traits of story protagonists into their self-concept (Isberner et al, 2019;Sestir & Green, 2010). Nonetheless, stronger arguments presented in a story still appear more convincing than weak arguments, especially among skeptical individuals (Appel et al, 2019).…”
Section: Transportationmentioning
confidence: 99%